Negative Symptom Domains Are Associated With Verbal Learning in Adolescents With Early Onset Psychosis - Mørch-Johnsen, Lynn; Smelror, Runar Elle; Andreou, Dimitrios; Barth, Claudia; Johannessen, Cecilie; Wedervang-Resell, Kirsten; Wortinger, Laura A.; Díaz, Ricardo; Victoria, Gamaliel; Ueland, Torill; Andreassen, Ole A.; Myhre, Anne M.; et al. (Frontiers in Psychiatry, 2022)
Background: Early-onset psychosis (EOP) is among the leading causes of disease burden in adolescents. Negative symptoms and cognitive deficits predicts poorer functional outcome. A better understanding of the association between negative symptoms and cognitive impairment may inform theories on underlying mechanisms and elucidate targets for development of new treatments. Two domains of negative symptoms have been described in adult patients with schizophrenia: apathy and diminished expression, however, the factorial structure of negative symptoms has not been investigated in EOP. We aimed to explore the factorial structure of negative symptoms and investigate associations between cognitive performance and negative symptom domains in adolescents with EOP. We hypothesized that (1) two negative symptom factors would be identifiable, and that (2) diminished expression would be more strongly associated with cognitive performance, similar to adult psychosis patients. Methods: Adolescent patients with non-affective EOP (n=169) were included from three cohorts: Youth-TOP, Norway (n=45), Early-Onset Study, Norway (n=27) and Adolescent Schizophrenia Study, Mexico (n=97). An exploratory factor analysis was performed to investigate the underlying structure of negative symptoms (measured with the Positive and Negative Syndrome Scale (PANSS)). Factor-models were further assessed using confirmatory factor analyses. Associations between negative symptom domains and six cognitive domains were assessed using multiple linear regression models controlling for age, sex and cohort. The neurocognitive domains from the MATRICS Consensus Cognitive Battery included: speed of processing, attention, working memory, verbal learning, visual learning, and reasoning and problem solving. Results: The exploratory factor analysis of PANSS negative symptoms suggested retaining only a single factor, but a forced two factor solution corroborated previously described factors of apathy and diminished expression in adult-onset schizophrenia. Results from confirmatory factor analysis indicated a better fit for the two-factor model than for the one-factor model. For both negative symptom domains, negative symptom scores were inversely associated with verbal learning scores. Conclusion: The results support the presence of two domains of negative symptoms in EOP; apathy and diminished expression. Future studies on negative symptoms in EOP should examine putative differential effects of these symptom domains. For both domains, negative symptom scores were significantly inversely associated with verbal learning.